Unveiling Illegal Marriages in Aceh: Examining the Role of Unofficial Qadi - Ramli, Misran; Rahmatillah, Syarifah; Nurdin, Abidin; Auliana, Nurul (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2024)
In Acehnese communities, particularly in Bayu Village, illegal marriages conducted by unofficial qadi have been identified. These marriages are often carried out in secrecy, making it difficult to verify whether they meet the pillars and conditions of marriage according to Islamic law. The study aimed to examine the practice of illegal marriages conducted by the community of Bayu Village, Nanggroe Aceh Darussalam Province, from the perspective of Islamic family law. The research employed an empirical legal research method using a qualitative descriptive approach. The findings found out several cases of illegal marriages performed by unofficial qadi in Bayu Village. Couples intending to marry are required to fulfill specific conditions set by the qadi, including providing identity cards (KTP) of the prospective spouses, passport-sized photographs of the couple, witnesses, a dowry (mahr), and a guardian (wali) from the bride’s side. The prevalence of illegal marriages is from the community's limited understanding of the importance of marriage registration. From the perspective of Islamic family law, marriages conducted with unofficial qadi in Bayu Village constitute a deviation from religious principles, a violation of government regulations, and have negative implications for the community.